Cover Feature: The Open Polarimeter: A High‐Resolution Instrument Made from Inexpensive Optomechanical Parts (Chemistry ‐ Methods 3/2021). Issue 3 (24th February 2021) - Harvie, Andrew J.; de Mello, John C.
Abstract : The Cover Feature shows the build instructions for the Open Polarimeter ("Opol") – a high‐resolution chemical polarimeter formed from a small number of inexpensive optomechanical parts. The complete instrument can be assembled from scratch in just two days for less than US$250, using only a 3D‐printer and a benchtop milling machine. Despite its low cost, Opol achieves a high accuracy of a few millidegrees, comparable to far costlier commercial instruments. More information can be found in the Full Paper by John C. de Mello et al .